FORMULATION AND OPTIMIZATION OF CARBOPOL AND ETHYL CELLULOSE AS FLOATING-MUCOADHESIVE SYSTEM OF DILTIAZEM HYDROCHLORIDE TABLET BY FACTORIAL DESIGN - Eka Deddy Irawan; Lusia Oktora Ruma Kumala Sari; Andreas Henry Prasetyo (UPT Penerbitan Universitas Jember)
Hypertension is a degenerative disease that eachyear has increased the number of patients. Numberof patients in Indonesia is estimated at 15 millionpeople. Nearly 50% of patients suffering fromhypertension are not aware that tends to be severehypertension (Syahrini et al., 2012).Diltiazem Hydrochloride (HCl) is an antihypertensivedrug used 3-4 times a day with doses of 30-60 mg(UBM Medica, 2012). Diltiazem HCl has a half life of3-5 hours (Sweetman, 2009) with the mainabsorption area in the upper stomach (Kapil et al.,2012) that can be formulated into sustained releasedosage gastro retentive system.The system created is a combination of floatingmucoadhesive.The combination of these systems isexpected to overcome the shortcomings of thesystem when used alone. Floating system floats overthe surface of gastric contents when the stomach isfull but at the time stomach is emptied and thetablet reaches the pylorus the bouyancy of thedosage may be decreased. If the stomach is full,mucodhesive dosage form not properly adheres maybe passage the pylorus due to peristalticmovements of the stomach (Gaykar et al., 2013).Polymer is one of the essential ingredients toproduce a floating-mucoadhesive system that meetsthe requirements. The polymer used is acombination of Carbopol and ethyl cellulose. Thecombination of hydrophilic and hydrophobicpolymers proved able to control the rate of drugrelease with high solubility (Nanjwade et al., 2011).